Long-term safety and efficacy of anti-GM-CSF otilimab in patients with rheumatoid arthritis: long-term extension of three phase 3 randomised trials (contRAst X) - Tsutomu Takeuchi; Iain B McInnes; Peter C Taylor; Roy M Fleischmann; Vibeke Strand; Michael E Weinblatt; David Brooks; Tatsuya Atsumi; Paula Curtis; Marguerite Bracher; Anubha Gupta; Didier Saurigny; et al. (BMJ Open)
Objectives To investigate the long-term safety and efficacy of otilimab, an antigranulocyte-macrophage colony-stimulating factor monoclonal antibody, for patients with rheumatoid arthritis (RA).Methods ContRAst X (NCT04333147) was a phase 3, multicentre, long-term extension trial. Patients with RA aged ≥18 years who completed a qualifying contRAst trial (contRAst 1–3) and who the investigator thought might benefit from long-term otilimab treatment were eligible to enter contRAst X. Patients who received otilimab (90 mg/150 mg) in their qualifying trial maintained the same dose; patients who received tofacitinib or sarilumab were rerandomised 1:1 to either otilimab dose. Patients could continue background conventional synthetic disease-modifying antirheumatic drugs. The primary objective was long-term safety (up to 4 years).Results Of the 2916 patients who entered contRAst X, 2915 received otilimab (exposure range: 7–896 days); the majority were withdrawn due to early trial termination. For otilimab 90 mg and 150 mg, the incidence of adverse events (AEs) was 62% (n=902/1456) and 64% (n=931/1459), the incidence of AEs of special interest was 8% (n=120/1456) and 7% (n=95/1459) and the incidence of serious AEs was 8% (n=123/1456) and 8% (n=114/1459), respectively. There were no instances of pulmonary alveolar proteinosis (PAP), active tuberculosis (TB), TB reactivation or serious hypersensitivity reactions. The proportions of clinical disease activity index low disease activity responders remained relatively stable throughout, with no apparent reduction following the switch from tofacitinib/sarilumab to otilimab.Conclusion No new safety signals or instances of PAP were associated with long-term (≤2.5 years) treatment with otilimab.Trial registration number ClinicalTrials.gov: NCT04333147.